Analysis of financial investments using financial indicators Applied in the Middle East Bank of Iraq for investment For the fiscal period 2007-2009 - علي, ابراهيم محمد; عبد الله, نور عبد الرزاق (Journal of Economics and Administrative Sciences, 2012)
The research explain the analysis of finance investments through  analyze the finance tables for commercial banks, by using the pointers to indicate the limits of economical benefit for these investments, and fix the negative deviations and as well positive, for the purpose of  diagnostic the negative (disadvantage) and develop the advantage deviation, For the importance of finance investments in the development operation and economical growth, further to that the finance investments is represent one of the most activities in the commercial banks in which aim the adequate incomes as a result of the commercial banks act to receipt the banks deposits and then make it growth and develop through  commercial advantage operations in the local markets and  investments , and directed these money in the proper  investment fields .